A novel ternary hybrid electromagnetic wave-absorbing composite based on BaFe11.92(LaNd)0.04O19-titanium dioxide/multiwalled carbon nanotubes/polythiophene. (29th September 2015) - Hong, Xiaowei; Xie, Yu; Wang, Xiaoying; Li, Mingjun; Le, Zhanggao; Gao, Yunhua; Huang, Yan; Qin, Yuancheng; Ling, Yun
Abstract: We report a novel ternary magnetic-conductive hybrid material with high conductivity, good magnetism, high stability and good wave-absorption. The hybrid material is based on doped barium ferrite (BF)-titanium dioxide (TD) and multiwalled carbon nanotubes (MCNTs) coated by polythiophene (PTh) matrix. The BF-TD/MCNTs/PTh composites were synthesized through in-situ chemical polymerization of thiophene in the presence of the BF-TD composites and MCNTs. The resulting composites were characterized by Fourier transform infrared (FT-IR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscopy (TEM), four-probe conductivity tester, vibrating sample magnetometer (VSM) and network analyzer. XRD and FT-IR indicated that the BF-TD/MCNTs/PTh composites were successfully synthesized with strong interactions among constituents. DTA-TGA analysis suggested that the decomposition of BF-TD/MCNTs/PTh composites included three stages. The first two stages were in accordance with the decomposition of BF-TD composites. The third stage was attributed to the decomposition of polythiophene. SEM and TEM demonstrated that BF-TD and MCNTs were well coated by polythiophene. The electromagnetic parameters showed that polythiophene and MCNTs could significantly improve the conductivity and the wave-absorbing performance of the BF-TD composites. When the MCNT content was 20 wt.% and the ratio of the barium ferrite to titanium dioxide was 4:5, BF-TD/MCNTs/PTh composites exhibited the best wave-absorbing performance.